Effect of Digoxin Use Among Medicaid Enrollees With Atrial Fibrillation. (May 2017) - Adedinsewo, Demilade; Xu, Junjun; Agasthi, Pradyumna; Oderinde, Adesoji; Adekeye, Oluwatoyosi; Sachdeva, Rajesh; Rust, George; Onwuanyi, Anekwe
Abstract : Background—: Recently published analysis of contemporary atrial fibrillation (AF) cohorts showed an association between digoxin and increased mortality and hospitalizations; however, other studies have demonstrated conflicting results. Many AF cohort studies did not or were unable to examine racial differences. Our goal was to examine risk factors for hospitalizations and mortality with digoxin use in a diverse real-world AF patient population and evaluate racial differences. Methods and Results—: We performed a retrospective cohort analysis of claims data for Medicaid beneficiaries, aged 18 to 64 years, with incident diagnosis of AF in 2008 with follow-up until December 31, 2009. We created Kaplan–Meier curves and constructed multivariable Cox proportional hazard models for mortality and hospitalization. We identified 11 297 patients with an incident diagnosis of AF in 2008, of those, 1401 (12.4%) were on digoxin. Kaplan–Meier analysis demonstrated an increased risk of hospitalization with digoxin use overall and within race and heart failure groups. In adjusted models, digoxin was associated with an increased risk of hospitalization (adjusted hazard ratio, 1.54; 95% confidence interval, 1.39–1.70) and mortality (adjusted hazard ratio, 1.50; 95% confidence interval, 1.05–2.13). Overall, blacks had a higher risk of hospitalization but similar mortality when compared with whites regardless of digoxin use. We found no significant interaction between race and digoxin use for mortality ( P =0.4437) and hospitalization ( P =0.7122). Conclusions—: Our study demonstrates an overall increased risk of hospitalizations and mortality with digoxin use but no racial/ethnic differences in outcomes were observed. Further studies including minority populations are needed to critically evaluate these associations. Abstract : Supplemental Digital Content is available in the text.